Fundamentals of Entrepreneurship (ENT300) : Case Study DA.DI.DU Borneo Haircut / Asrizal Hakim Othman … [et al.] - Othman, Asrizal Hakim; Dickie, Veronica Wilda; Muhidin, Saidatul Anisa; Collin, Davina Elvie; Angin, Evelyn Kurash (2019)
Da.Di.Du Borneo Haircut offers haircut and saloon services for customers. They provides various kind of unique haircuts and the customers can choose according to their preferences. Mostly demand for the haircuts are during annual festival such as Hari Raya, Hari Gawai and Chinese New Year.Other than that,they also targeting students because it is placed near two universities which are UiTM and UNIMAS.Thus, Da.Di.Du Borneo Haircut have 7 branches in Sarawak including their headquarters.